2016
DOI: 10.1002/clc.22521
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Ejection Fraction Predicts Severity of Posttraumatic Stress Disorder in Patients With Implantable Cardioverter‐Defibrillators

Abstract: Background: Implantable cardioverter-defibrillators (ICD) have provided effective therapy for fatal arrhythmia. However, ICD patients are known to develop psychological problems, such as posttraumatic stress disorder (PTSD), if they have experienced potentially fatal arrhythmia and ICD shocks. Little is known about the factors influencing PTSD in ICD patients. Hypothesis: Echocardiographic cardiac-function parameters might relate to psychological problems, especially PTSD, in ICD patients. Methods: A total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
(54 reference statements)
0
3
1
Order By: Relevance
“…51 Moreover, Sawatari et al found similar negative correlation value to our results between LVEF levels and IES-R scores in patients with implantable cardioverter-defibrillators (r = -0.36, p = 0.045). 52 Although we observed lower correlations in total patient population, we found higher significantly correlation coefficients between LVGLS values and IES-R total, and intrusion scores in patients admitted with severe pneumonia and also having comorbidity. Therefore, we may speculate that patients with comorbid diseases, or recovering from the severe illness with challenging treatment history of COVID-19 may have experienced more psychological stress reactions which may have had a more negative impact on subclinical myocardial systolic functions.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…51 Moreover, Sawatari et al found similar negative correlation value to our results between LVEF levels and IES-R scores in patients with implantable cardioverter-defibrillators (r = -0.36, p = 0.045). 52 Although we observed lower correlations in total patient population, we found higher significantly correlation coefficients between LVGLS values and IES-R total, and intrusion scores in patients admitted with severe pneumonia and also having comorbidity. Therefore, we may speculate that patients with comorbid diseases, or recovering from the severe illness with challenging treatment history of COVID-19 may have experienced more psychological stress reactions which may have had a more negative impact on subclinical myocardial systolic functions.…”
Section: Discussioncontrasting
confidence: 64%
“…51 Moreover, Sawatari et al found similar negative correlation value to our results between LVEF levels and IES-R scores in patients with implantable cardioverter-defibrillators (r = -0.36, p = 0.045). 52 …”
Section: Discussionmentioning
confidence: 99%
“… Newman et al (2011) surveyed 241 patients with acute coronary syndromes and reported that those with PTSD symptoms (18%) were higher than those without PTSD symptoms (82%) (LVEF: 53.0 vs. 46.1%). In addition, ( Sawatari et al, 2016 ) found that LVEF level was a useful to predict of PTSD severity. Therefore, early active treatment should be carried out to improve the cardiac function of severe AMI patients to promote the early recovery, reduce psychological stress, and prevent, or reduce PTSD, or both.…”
Section: Discussionmentioning
confidence: 99%
“…To date, very few published studies have examined cardiac function in PTSD patients (2,6,8). Sawatari et al (27) found that left ventricular ejection fraction (LVEF), an indication of systolic function, was related to the severity of PTSD. It remains unknown whether LV diastolic function is impaired in patients with PTSD.…”
Section: Introductionmentioning
confidence: 99%